2019
DOI: 10.26905/afr.v2i2.3717
|View full text |Cite
|
Sign up to set email alerts
|

Bank Size, Risk and Market Discipline with A Deposit Insurance: Evidence of Banking in Indonesia

Abstract: The Indonesian banking system has implemented a deposit guarantee. Deposit guarantees are carried out in order to provide a sense of security for customers. Moral hazard tends to be higher in the banking industry This study aims to examine the relationship of bank characteristics with market discipline. Bank characteristics include: capital, bank risk, profitability, efficiency and bank size. The population in this study is banks in Indonesia. The sample selection uses a purposive sampling method. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…NPL/GL has a significant (at the 99% level) and positive relationship with cost because such loans worry depositors and add pressure on a bank. This result is aligned with past studies (Abou-El-Sood, 2016; Haryanto et al , 2019). OH/TA means managers are less efficient, so depositors impose a higher cost of funds on such banks.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…NPL/GL has a significant (at the 99% level) and positive relationship with cost because such loans worry depositors and add pressure on a bank. This result is aligned with past studies (Abou-El-Sood, 2016; Haryanto et al , 2019). OH/TA means managers are less efficient, so depositors impose a higher cost of funds on such banks.…”
Section: Resultssupporting
confidence: 93%
“…Haryanto et al (2019) have found positive relationships of market discipline with bank size and profitability. Arnold et al (2016) have found that depositors remain vigilant and sensitive to a bank’s stability, even when there is blanket coverage offered by the government.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Firstly, Indonesia is one of the countries that has implemented a deposit guarantee in its banking system. Deposit insurance is offered to provide customers (depositors) with a sense of security in the banking system where the moral hazard tends to be higher (Haryanto et al, 2019). Secondly, banks are still the main financial intermediaries in Indonesia (Trinugroho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, their study does not directly investigate the role of financial literacy in imposing effective market discipline. Hamada (2011), Haryanto et al (2019, and Suliyono and Risfandy (2021) conduct prior research examining market discipline in the Indonesian banking industry. Most studies in the field of market discipline have only focused on companies' financial data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation